Employer Branding, Leadership Behaviour, and Generation Z Career Intentions: The Mediating Role of Employer Attractiveness among Final-Year Students in Jambi Province, Indonesia - Musthafa Luthfi; Noviardi Ferzi (Ilomata International Journal of Management, 2026)
This study examines how employer branding and leadership behavior influence Generation Z’s career intentions during their transition from higher education to employment. In increasingly competitive labor markets, organizations rely on credible signals to shape job seekers’ perceptions; drawing on signaling theory, this study conceptualizes employer branding and leadership behavior as complementary signals that influence career intentions through employer attractiveness. Prior research has largely treated employer branding as an isolated predictor, with limited attention to leadership behavior as a parallel signal and few studies testing their combined effects within a mediation framework. Addressing this gap, the study employs a structured survey of 400 final-year undergraduate students from five accredited universities in Jambi Province, Indonesia, and analyzes the data using Structural Equation Modeling (SEM). The results indicate that employer branding significantly influences career intention (β = 0.373; p < 0.001), while leadership behavior shows a stronger effect (β = 0.532; p < 0.001). Both employer branding (β = 0.378; p < 0.001) and leadership behavior (β = 0.612; p < 0.001) significantly affect employer attractiveness, which in turn predicts career intention (β = 0.609; p < 0.001). Mediation analysis reveals partial mediation, as both direct and indirect effects remain significant, with indirect effects of employer branding (β = 0.230; p < 0.001) and leadership behavior (β = 0.373; p < 0.001) on career intention through employer attractiveness. Given the cross-sectional design, the findings indicate associations rather than causality; however, they provide context-sensitive insights into signaling mechanisms in environments with limited access to organizational information and suggest that organizations may enhance employer attractiveness to potentially improve early-stage recruitment outcomes among Generation Z.